Change in Emotion Regulation Strategy Use and Its Impact on Adolescent Nonsuicidal Self-Injury: A Three-Year Longitudinal Analysis Using Latent Growth Modeling - Voon, D.; Hasking, Penelope; Martin, G. (American Psychological Association, 2014)
This longitudinal study examines the extent to which changes in the use of cognitive reappraisal, expressive suppression, and rumination impact on frequency, duration, and medical severity of nonsuicidal self-injury (NSSI) among adolescents. Data from 3,143 predominantly female high school students recruited from 40 Australian secondary schools were analyzed using latent growth curve modeling. Significant differences in the psychological factors between the 555 participants with a history of NSSI and non-self-injurers were reported at baseline. Self-injurers experienced significantly greater accumulation of life stressors over time compared with non-self-injurers. After controlling for adverse life events, psychological distress and other emotion regulation strategies, use of cognitive reappraisal at baseline was associated with less severe NSSI presentations, and slower growth in medical severity of NSSI over time. Findings indicate that while both cohorts have similar emotion regulation trajectories, adolescents who self-injure start off at a disadvantage and have a propensity to engage in less helpful processes that tend to heighten negative emotional states. Results recommend increasing focus on improving adolescents' frequency and skills in use of cognitive reappraisal in efforts to reduce NSSI among this population.